1973: Memories of a Lesbian Body – Reading Monique Wittig's Le Corps lesbien through Deleuze and Guattari's le corps sans organes. Issue 1 (February 2021) - Okumu, Robin
Abstract : This article reads Monique Wittig's Le Corps lesbien (1973) through Deleuze and Guattari's concepts of le corps sans organes (the body without organs; BwO) and devenir-femme, devenir-animal (becoming-woman, becoming-animal) in order to illuminate both Wittig's formal and figurative concerns and her larger literary objectives. The dismembered and dismember- ing lesbian lovers that Wittig describes in Le Corps lesbien illustrate a process of becoming-woman, becoming-animal and becoming-other that leads to a becoming-minoritarian and a renunciation of stratification and subjectification in the body without organs. This process is a celebration of dispersed, multiplicitous identity that exists in haecceities. Wittig's lesbian lovers undergo various becomings in the text to illustrate the multiplicity of possibilities as they move towards the BwO, and the text as a whole uses this BwO to resist and dismantle the hetero-patriarchal order.